TINJAUAN YURIDIS WANPRESTASI DALAM PERJANJIAN UTANG PIUTANG YANG TIDAK TERTULIS DALAM HUBUNGAN KEKERABATAN (ANALISIS PUTUSAN NOMOR : 35/Pdt.G/2016/Pn.Mlg.) - Debby Mutiara Silalahi; Egi Benaronta Purba; Rizki (The Juris, 2022)
The purpose of this research is to understand the position of an unwritten agreement in civil law and to understand the legal consequences of default in an unwritten agreement. This research uses normative juridical legal research and sourced from primary and secondary legal materials. The data technique used in this research is library research and access internet sites. The formulation of the problem in this research is: (1) How the position of the unwritten agreement in civil law? (2) How to regulate default in civil law? (3) How do judge’s consideration in decision number: 35/Pdt.G/2016/Pn.Mlg?. The result of this decision is that the judge decided to partially grant the plaintiff’s petitum, determine that the defendants have broken promises, demanded that the defendants pay the debt to the plaintiff, to pay court fees, and others. Based on the Judges’s decision, we can conclude that in making agreements we must fulfill all agreed achievements, so as not to harm others.